Nonholonomic frames for Finsler space with deformed infinite series of (α,β) metric - Brijesh Kumar Tripathi; V. K. Chaubey (Journal of Hyperstructures)
The purpose of present paper to determine the Finsler spaces due to deformation of special Finsler  (α, β) -metric. Consequently, we obtained the non-holonomic frame with the help of α2=aij(x)yiyj, one form metric β=bi(x)yi and infinite series of (α, β) metric such as the forms I. ( β4 /(β-α )2 ) + α2 =F12+F22  i.e. sum of the square of infinite series of (α, β) -metric and square of Riemannian metric  II. ( β4 /(β-α )2 ) + β2 =F12+F32 i.e. sum of the square of infinite series of  (α, β) -metric and square of 1-form metric.